1994
DOI: 10.1007/bf00352253
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear position of pericentromeric DNA of chromosome 11 appears to be random in GO and non-random in G1 human lymphocytes

Abstract: The nuclear position of pericentromeric DNA of chromosome 11 appears to be random in G0 and non-random in G1 human lymphocytes Hulspas, R.; Houtsmuller, A.; Krijtenburg, P.-J.; Bauman, J.G.J.; Nanninga, N. Published in: Chromosoma DOI:10.1007/BF00352253 Link to publication Citation for published version (APA):Hulspas, R., Houtsmuller, A., Krijtenburg, P-J., Bauman, J. G. J., & Nanninga, N. (1994). The nuclear position of pericentromeric DNA of chromosome 11 appears to be random in G0 and non-random in G1 human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…From a physiological point of view, these observations are complementary to the growing evidence for a territorial interphase chromosome organization (1,2,5). Specific chromatin domains occupy distinct, nonrandom, spatial positions as reported previously (9,10). Whether there is a correlation between gene expression and chromosome repositioning remains to be investigated further because some results indicate that both active and inactive genes localize preferentially in the periphery of chromosome territories (30).…”
Section: Results and Discussion P21supporting
confidence: 72%
See 1 more Smart Citation
“…From a physiological point of view, these observations are complementary to the growing evidence for a territorial interphase chromosome organization (1,2,5). Specific chromatin domains occupy distinct, nonrandom, spatial positions as reported previously (9,10). Whether there is a correlation between gene expression and chromosome repositioning remains to be investigated further because some results indicate that both active and inactive genes localize preferentially in the periphery of chromosome territories (30).…”
Section: Results and Discussion P21supporting
confidence: 72%
“…Factors involved in transcript processing are identified within discrete foci in nuclei (7,8). Spatial rearrangement of chromatin was recently observed during the cell cycle (9,10). Studies in Drosophila demonstrate a position effect variegation with striking consequences on gene expression depending upon the gene's distance from the centromere and its association with a block of heterochromatin (11)(12)(13).…”
mentioning
confidence: 99%
“…In the present study we found that about 90% of centromeres were located in the periphery of human lymphocyte nuclei in G0, while about half of centromeres were located in the periphery and half in the nuclear interior, including adjacent to the nucleoli, of lymphocyte nuclei in early G1. Hulspas et al (1994) carried out FISH with a human chromosome 11 centromere-specific probe in both nonstimulated lymphocytes harvested directly from peripheral blood and in cultured, PHA-stimulated human lymphocytes. Laser confocal microscopy using the nuclear center as a reference point revealed that the distribution of the chromosome 11 centromeres appeared to be random during the G0 stage, while most, if not all, centromeres were found at the nuclear periphery in G1.…”
Section: Kinetochore Movements In Cycling Cells and Upon Exit From Thmentioning
confidence: 99%
“…Centromeres provide another example where major movements have been observed in nuclei of both postmitotic cells (Manuelidis 1985;Alcobia et al 2000;Martou and De Boni 2000;Solovei et al 2004a) and cycling cells (Bartholdi 1991;Ferguson and Ward 1992;Weimer et al 1992;Vourc'h et al 1993;Hulspas et al 1994). Previous studies of the distribution of centromeres/kinetochores in cycling and non-cycling cell types had important technical limitations, including the unequivocal discrimination of non-cycling cells (G0) from cells at different stages and substages of interphase (see Discussion).…”
Section: Introductionmentioning
confidence: 99%
“…The X and Y chromosomes occupy restricted domains on opposite poles of the nucleus in Sertoli cells (Armstrong et al 1994). There are several examples in which the relative positions of centromeres and telomeres in relation to the nuclear envelope are clearly non-random (Vourc'h et al 1993;Hulspas et al 1994;Scherthan et al 1996). However, the spherical shape of the interphase nucleus makes it hard to determine precisely the relative positions of chromosomes.…”
Section: Introductionmentioning
confidence: 99%